Improved group-specific primers based on the full SILVA 16S rRNA gene reference database - Pfeiffer, S.; Pastar, M.; Mitter, B.; Lippert, K.; Hackl, E.; Lojan, P.; Oswald, A.; Sessitsch, A. (Wiley, 2014)
Quantitative PCR (qPCR) and community fingerprinting methods, such as the Terminal Restriction Fragment Length Polymorphism (T‐RFLP) analysis, are well‐suited techniques for the examination of microbial community structures. The use of phylum‐ and class‐specific primers can provide enhanced sensitivity and phylogenetic resolution as compared with domain‐specific primers. To date, several phylum‐ and class‐specific primers targeting the 16S ribosomal RNA gene have been published. However, many of these primers exhibit low discriminatory power against non‐target bacteria in PCR. In this study, we evaluated the precision of certain published primers in silico and via specific PCR. We designed new qPCR and T‐RFLP primer pairs (for the classes Alphaproteobacteria and Betaproteobacteria, and the phyla Bacteroidetes, Firmicutes and Actinobacteria) by combining the sequence information from a public dataset (SILVA SSU Ref 102 NR) with manual primer design. We evaluated the primer pairs via PCR using isolates of the above‐mentioned groups and via screening of clone libraries from environmental soil samples and human faecal samples. As observed through theoretical and practical evaluation, the primers developed in this study showed a higher level of precision than previously published primers, thus allowing a deeper insight into microbial community dynamics.